Democracy, Threat Reconfiguration, and South American Peace - Battaglino, Jorge (2015)
This paper claims that South American democracies have demonstrated a notable predisposition toward bilateral agreements, toward the search for arbitration/mediation, and toward the establishment of inter-democratic regional institutions. ese traits have favored the resolution of the majority of regional conicts, or if not resolution, then conict management through dierent institutions. Likewise, the proliferation and consolidation of regional peace has precipitated a phenomenon of democratic peace that went unanticipated by the literature: the reconguration of threats, which, through its own momentum, reinforces South American peace.